Workforce Planning to Improve Employee Performance at PT. Primajasa Perdanaraya Utama, Bandung - Delanur Hasanah; Diki Achmad Hidayat; Citra Zahra Viramaida; Dhiya Majdiy; Resya Dwi Marselina (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the role of workforce planning in improving employee performance at PT. Primajasa Perdanaraya Utama Bandung using an empirical qualitative case study approach. Data were collected through semi structured interviews, direct observation, and document analysis involving human resource managers, operational supervisors, and frontline employees. The findings indicate that workforce planning practices are reflected in recruitment, training, employee development, and performance control systems that contribute to improved employee performance in terms of work quality, task execution, and responsibility. However, the effectiveness of workforce planning is influenced by internal factors such as turnover stability, managerial policy orientation, data readiness, and organizational coordination, as well as external factors including digital transformation, regulatory changes, economic conditions, and industry competition. The study further reveals that although workforce planning improves employee discipline and operational consistency, it remains largely reactive and lacks structured forecasting and integrated data systems. These limitations reduce its strategic impact on long term human resource development. The study concludes that strengthening HRIS implementation and forecasting based workforce planning is essential for sustainable performance improvement.